The role of mechanobiology on the Schwann cell response: A tissue engineering perspective - Manganas, Phanee; Kavatzikidou, Paraskevi; Kordas, Antonis; Babaliari, Eleftheria; Stratakis, Emmanuel; Ranella, Anthi (Frontiers in Cellular Neuroscience, 2022)
Schwann cells, the glial cells of the peripheral nervous system (PNS), do not only form myelin sheaths thereby insulating the electrical signal propagated by the axons, but also play an essential role in the regeneration of injured axons. Schwann cells are inextricably connected with their extracellular environment and the mechanical stimuli that are received determine their response during development, myelination and injuries. To this end, the mechanobiological response of Schwann cells is being actively researched, as it can determine the suitability of fabricated scaffolds for tissue engineering and regenerative medicine applications. There is growing evidence that Schwann cells are sensitive to changes in the mechanical properties of the surrounding environment (such as the type of material, its elasticity and stiffness), different topographical features provided by the environment, as well as shear stress. In this review, we explore how different mechanical stimuli affect Schwann cell behaviour and highlight the importance of exploring many different avenues when designing scaffolds for the repair of PNS injuries.